Adaptive Modelling of Multipath Communication Channels Based on the Least Mean Square Algorithm - Dhimas Arief Dharmawan (Journal of Electrical Technology UMY, 2017)
The objective of this research is to design an adaptive model for multipaths communication channels. To evaluate the performance of the model, the authors used two indicators, namely the attainment of a minimum value of error signals in the form of interface and echo on the channel, and Filter Finite Impulse Response (FIR) has the same form of equation as the channel equation used. This adaptation process uses the Least Mean Square (LMS) algorithm. The LMS algorithm is known as a simple algorithm, which is fast computation time and the computation results are quite satisfying. In this study, the authors used Simulink software on Matlab. In general, this research is divided into three stages, namely modeling multipaths communication channels as an adaptive system, designing an adaptive system model on Simulink, and designing a simulation of 250 iterations. After obtaining the simulation results in the form of errors and weight of the FIR filter, it is observed that both of the results have met the requirements of the indicators of the success of this study. With 250 iterations used, satisfactory results were obtained in the form of the fulfillment of all indicators of the success of this study.